Occurence of Blissus leucopterus on pasture in Rio do Janeiro State - Pereira, Roberto Peixoto; Silva, Sebastião Carlos da (Pesquisa Agropecuaria Brasileira, 2014)
The chinch-bug Blissus leucopterus (Say, 1832) (Hemiptera: Lygaeidae) is considered the most important pest of gramineous in North America, and was first recorded in Brazil in 1975, in the state of Minas Gerais. Its occurrence was observed in the state of Rio de Janeiro since 1980 causing damage in Tanner-grass and Tangola-grass pastures. Also Angola-grass was observed showing resistance to chinch-bug.